Psycodinamic Approach - M. Budi Susanto; Ilham Mukhamada; Helmi Zulkarnain; Mochammad Isa Anshori (CV. Aksara Global Akademia, 2023)
This research is a qualitative research. Data collection was carried out using the literature study method. This study aims to find out the characters who play a role in the theory of psychodynamic development, to find out the phases of development according to the theory put forward by Sigmund Freud, and to find out what personality theories exist in psychodynamic theory. The psychodynamic theory was discovered by Sigmund Freud (1856-1939). Many experts then took part in using the psychoanalytic paradigm to develop their personality theory, such as: Carl Gustav Jung, Alfred Adler, as well as other figures such as Anna Freud, Karen Horney, Eric Fromm, and Harry Stack Sullivan. The phases of development according to Freud are: Oral phase (oral stage): 0 to about 18 months, Anal phase (anal stage): about 18 months to 3 years of age, Phallic phase (phallic stage): approx. 3 to 6 years of age, latency stage: approx. 6 to puberty, and genital stage: occurs from the time an individual enters puberty and beyond. Personality theory according to Freud consists of three namely: id (biological aspect), ego (psychological aspect) and superego (sociological aspect). Psychodynamic theory or clinical tradition departs from two basic assumptions. First, humans are part of the animal world. Second, humans are part of the energy system.